Principles and practice of Chemotherapy - Qaiser Baig, Mirza (India : Jaypee Brothers Medical Publishers, 2012)
Este libro es una guía completa de los principios y la práctica de la gestión del cáncer. Comenzando con una introducción a la oncología médica y su manejo, las siguientes secciones examinan tipos comunes de cáncer y sus terapias de quimio y radiación. Más de 200 imágenes e ilustraciones están incluidas para ayudar a entender.
SECTION-A: MEDICAL ONCOLOGY 1. Concepts of Cancer Chemotherapy 2. Chemotherapeutic Drugs 3. Targeted Cancer therapy 4. New Hope with gene therapy 5. Side efeccts of chemotherapy Más otros títulos... SECTION-B: GENERALMANAGEMENT IN ONCOLOGY 7. Management of Cancer pain 8. Management of Anemia 9. Management of Bleeding in Cancer Patient´s 10. Role of steroids in cancer más otros temas... SECTI-C: COMMON CANCER AND ITS MANAGEMENT 12. Management of cervical cancer 13. Breast cancer management 14. Palliative treatment in breast cancer 15. Head and neck cancer 16. Ovarian cancer Mas otros títulos.... SECTION-D: RADIATION ONCOLOGY 27 Radioactivity 28. Measureent of X-ray 29. Principles of radiation therapy 30. Time, dose and fractionation in raditherapy 31. Effects of radiation on normal human tissue Más otros títulos....
Incluye índice general
Incluye bibliografía
Keywords: QUIMIOTERAPIA; FARMACOLOGIA; ONCOLOGIA; CANCER